2014
DOI: 10.1021/ac403397r
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of 3D Printing and Its Potential Impact on Biotechnology and the Chemical Sciences

Abstract: Nearing 30 years since its introduction, 3D printing technology is set to revolutionize research and teaching laboratories. This feature encompasses the history of 3D printing, reviews various printing methods, and presents current applications. The authors offer an appraisal of the future direction and impact this technology will have on laboratory settings as 3D printers become more accessible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
1,113
1
37

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,462 publications
(1,153 citation statements)
references
References 153 publications
2
1,113
1
37
Order By: Relevance
“…The paperbased iCVD substrate (1 × 1 cm) was soaked in 1, 1.5, and 3% (wt/vol) sodium alginate (FMC biopolymer), respectively. Samples at the desired time points (10,20,30, and 60 min) were collected and imaged using AM413MT Dino-Lite X (Dino-Lite). The hydrogel thickness was analyzed as three random points were chosen, and the average was calculated by DinoCapture 2.0 (Dino-Lite).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The paperbased iCVD substrate (1 × 1 cm) was soaked in 1, 1.5, and 3% (wt/vol) sodium alginate (FMC biopolymer), respectively. Samples at the desired time points (10,20,30, and 60 min) were collected and imaged using AM413MT Dino-Lite X (Dino-Lite). The hydrogel thickness was analyzed as three random points were chosen, and the average was calculated by DinoCapture 2.0 (Dino-Lite).…”
Section: Methodsmentioning
confidence: 99%
“…These fabrication processes, however, possess limitations for organlike structure productions. Although recent progress in tissue engineering has focused on using 3D printer schemes, there are still limitations such as the shortage of appropriate printing materials and technical challenges related to the sensitivity of living cells (10)(11)(12).…”
mentioning
confidence: 99%
“…Recent reviews describe state of the art 3D-printing for microfluidics applications. 18,19 All the demonstrations of 3D-printed microfluidics so far employ active flow control (usually pneumatic or centrifugal pumps). The resolution currently available with consumer grade 3D-printers is typically ≥ 200 µm 20,21 with ~ 1 µm surface roughness.…”
Section: D-printed Microfluidicsmentioning
confidence: 99%
“…Microfluidic devices are used in fields such as bioanalysis, materials engineering, and chemistry (Femmer et al 2015;Gross et al 2014;Shah et al 2008;Shirk et al 2013;Utada et al 2007;Ye et al 2015). These devices are especially useful in bioanalysis because they have the ability to manipulate relatively small volumes of fluid, requiring small samples from a test subject.…”
Section: Introductionmentioning
confidence: 99%
“…3D-printed templates also allow for accelerated testing and modification of device designs; modifications can be added to the template file and printed out immediately (Gross et al 2014;O'Neill et al 2014). MacDonald, et al (2002) have demonstrated a method to create microfluidic devices in PDMS using solid object printing.…”
Section: Introductionmentioning
confidence: 99%